Undergraduate Students’ Perception of Lecturers Written Corrective Feedback in the Process of Writing Undergraduate Thesis - Zulva Rahmadhani; Astri Hapsari (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
This survey study aims to identify EFL undergraduate students' perception of the practice of written corrective feedback (WCF) for their undergraduate thesis drafts. 60 students enrolling in Thesis Proposal Defense coursework agreed to participate in this study. This study used a 31-item questionnaire adopted from Marrs' (2016) Perceptions of Writing Feedback Scale (PoWF) questionnaire which describes four aspects: views/expectations of feedback, experiences with feedback, usefulness/value of feedback, and affect/emotions associated with feedback. The result of the mean score of the items indicates that students' perception is generally positive. The participants perceived written feedback as important in their writing. They also perceived that even though they have a good score, feedback is still meaningful. They value writing feedback and perceive it useful to help them to be better with their writing. Finally, in terms of affect and emotions associated with writing feedback, the findings revealed that the participants felt happy and confident when they were given writing feedback in their undergraduate thesis proposal draft. For further research, the researchers recommend further investigation into the relationship between students' self-efficacy in writing and their perception of writing feedback.